2006
DOI: 10.1126/science.1133568
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Neon from Genesis: Implications for the Lunar Noble Gas Record

Abstract: Lunar soils have been thought to contain two solar noble gas components with distinct isotopic composition. One has been identified as implanted solar wind, the other as higher-energy solar particles. The latter was puzzling because its relative amounts were much too large compared with present-day fluxes, suggesting periodic, very high solar activity in the past. Here we show that the depth-dependent isotopic composition of neon in a metallic glass exposed on NASA's Genesis mission agrees with the expected de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 20 publications
10
114
1
2
Order By: Relevance
“…1). Preliminary results from the Genesis mission (see Grimberg et al 2007) largely confirm the Apollo results. From the isotopic abundance measurements one derives an elemental ratio He/Ne = 530 ± 65.…”
Section: Introductionsupporting
confidence: 74%
“…1). Preliminary results from the Genesis mission (see Grimberg et al 2007) largely confirm the Apollo results. From the isotopic abundance measurements one derives an elemental ratio He/Ne = 530 ± 65.…”
Section: Introductionsupporting
confidence: 74%
“…Solar wind ions are bound to the solar magnetic field and, thus, all ions are implanted with equal velocity so that all SW noble gases ( Figure 5) (Grimberg et al, 2006). Analogous isotopic effect has been observed in SW He, Ne and Ar in the lunar regolith samples (e.g.…”
Section: Depth Profiles Of Light Noble Gasesmentioning
confidence: 73%
“…One-sigma error envelopes of 38 Ar/ 36 Ar ratios in all the samples are within error of air (figure 3; table 1), even in well-gas samples containing as much as 50 per cent mantle argon (Holland & Ballentine 2006 Benkert et al 1993) due to implantation fractionation analogous to that observed in Ne isotopes (Grimberg et al 2006).…”
Section: Non-radiogenic Argon: No Evidence Of a Solar Componentmentioning
confidence: 90%
“…Solar Ne has a 20 Ne/ 22 NeZ13.8 (Benkert et al 1993;Grimberg et al 2006), while the maximum observed trapped in meteorites is 20 Ne/ 22 NeZ12.5 (Black 1972;Wieler 2002;Trieloff et al 2000Trieloff et al , 2002. Models of terrestrial volatile acquisition invoking a major role for solar nebula gases are predicted to produce a mantle 20 Ne/ 22 New13.8.…”
Section: Neon: a Trapped Meteorite Origin For Terrestrial Mantle Volamentioning
confidence: 99%